Left internal carotid artery agenesis in a patient with headache - Leão, Inês Alice Teixeira; Rezende, C. H.; Gomes, J. B. L.; Almeida, R. F. (Headache Medicine, 2014)
Sometimes in clinical neurology, we diagnose a very rare case. We report on a patient who presented with crisis of headache and vomiting (clinically diagnose as migraine). Computed tomography (CT) scan of the head did not reveal any structural lesion. Magnetic resonance angiography showed absence of left internal carotid artery associated with absence of the left middle cerebral artery (MCA).